2015
DOI: 10.1007/s12630-015-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

The incidence, success rate, and complications of awake tracheal intubation in 1,554 patients over 12 years: an historical cohort study

Abstract: The incidence, success rate, and complications of awake tracheal intubation in 1,554 patients over 12 years: an historical cohort study Incidence, taux de réussite et complications de l'intubation trachéale chez 1554 patients éveillés sur une période de 12 ans: une étude de cohorte historique AbstractPurpose Awake tracheal intubation is one recommended option to address select situations in the management of a patient with an anticipated difficult airway. A scarcity of data exists on how often awake intubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
89
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 30 publications
7
89
1
2
Order By: Relevance
“…The main result was not surprising. If the method of preoperative evaluation was relatively constant during the 2002-2013 period, which is a reasonable assumption, we would then expect the incidence of recognized DAs to be constant, which is what Law et al 5 found. According to Law et al, 5 there was no intubation method (including video laryngoscopy) that was good enough (i.e., close to 100% effective) to replace and decrease the use of awake intubation for the patient with a recognized DA.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…The main result was not surprising. If the method of preoperative evaluation was relatively constant during the 2002-2013 period, which is a reasonable assumption, we would then expect the incidence of recognized DAs to be constant, which is what Law et al 5 found. According to Law et al, 5 there was no intubation method (including video laryngoscopy) that was good enough (i.e., close to 100% effective) to replace and decrease the use of awake intubation for the patient with a recognized DA.…”
mentioning
confidence: 68%
“…The second important concept inherent in the ASA-DA-G is that the practitioner should have several effective ''Plan Bs'' immediately available in case general anesthesia is induced, with or without paralysis, and the airway is indeed difficult to manage. This month's issue of the Journal features a study by Law et al 5 which shows that there was no significant change in the use of awake tracheal intubation (1.06% of 146,252 patients) at a large tertiary care centre in Canada over the studied years (2002-2013), even though there was a significant increase in the use of video laryngoscopy after the induction of general anesthesia over the same time period. The Law et al study 5 is a novel clear-cut scientific analysis of who is using which intubation technique for patients with a DA.…”
mentioning
confidence: 99%
See 3 more Smart Citations